Photosynthetic performance of mangroves Rhizophora mangle and Laguncularia racemosa under field conditions - Falqueto,Antelmo Ralph (2008)
In mature mangrove plants Rhizophora mangle L. and Laguncularia racemosa Gaerth. growing under field conditions, photosystem 2 (PS2) photochemical efficiency, determined by the ratio of variable to maximum fluorescence (Fν/Fm), increased during the day in response to salinity in the rainy seasons. During the dry season, fluorescence values (Fo) were higher than those observed in rainy season. In addition, Fo decreased during the day in both season and species, except for R. mangle during the dry season. A positive correlation among Fν/Fm and salinity values was obtained for R. mangle and L. Racemosa during the dry and rainy seasons, showing that photosynthetic performance is maintained in both species under high salinities. Carotenoid content was higher in L. Racemosa in both seasons, which represents an additional mechanism against damage to the photosynthetic machinery. The chlorophyll content was not affected by salinity in either species.